Effects of microstructure and crystallography on crack path and intrinsic resistance to shear-mode fatigue crack growth (Fracture and Structural Integrity, 2015)
The paper focuses on the effective resistance and the near-threshold growth mechanisms in theferritic-pearlitic and the pure pearlitic steel. The influence of microstructure on the shear-mode fatigue crackgrowth is divided here into two factors: the crystal lattice type and the presence of different phases.Experiments were done on ferritic-pearlitic steel and pearlitic steel using three different specimens, for whichthe effective mode II and mode III threshold values were measured and fracture surfaces were reconstructed inthree dimensions using stereophotogrammetry in scanning electron microscope. The ferritic-pearlitic andpearlitic steels showed a much different behaviour of modes II and III cracks than that of the ARMCO iron.Both the deflection angle and the mode II threshold were much higher and comparable to the austenitic steel.Mechanism of shear-mode crack behaviour in the ARMCO iron, titanium and nickel were described by themodel of emission of dislocations from the crack tip under a dominant mode II loading. In other testedmaterials the cracks propagated under a dominance of the local mode I. In the ferritic-pearlitic and pearliticsteels, the reason for such behaviour was the presence of the secondary-phase particles (cementite lamellas),unlike in the previously austenitic steel, where the fcc structure and the low stacking fault energy were the mainfactors. A criterion for mode I deflection from the mode II crack-tip loading, which uses values of the effectivemode I and mode II thresholds, was in agreement with fractographical observations.
Keywords: mode II and mode III cracks